Beamforming Networks for antenna array, useful inWiFi applications - Carlos Ramiro Peñafiel Ojeda; Luis Fernando Carrera Suárez; Diana Verónica Navarro Méndez; Mariano Baquero Escudero; Miguel Ferrando Bataller (NOVASINERGIA, 2018)
In this paper several types of beamforming networks have been presented, this proposalcan be used for an array antenna, which are used in several types of WiFi applications,IEEE 802.11b/g/draft-n. The first design corresponds to a 4x4 Butler Matrix for a reso-nance frequency at 2.45 GHz, depending on the port through which the signal is excited,it will be possible to obtain several variations in phase at the output ports (45◦, 135◦,-45◦and -135◦), the proposed Butler matrix has been optimized from a generalized ma-trix scheme, reducing the size through a simple overlap of multiple transmission linestoλ/4 at the central frequency. The second design corresponds to a Rotman lens witha characteristic resonance frequency of 5.8 GHz, with a maximum focal angle of 30◦,for this design has been used geometric optics concept, and the last design has beenmade for a frequency of 5.8 GHz using a slot array designed with Substrate IntegratedWaveguide technology.